‘Your Very Existence Goes Against Our Community Guidelines’: Interrogating norms of contributorship through poetic speech acts on Instagram - Nadegger, Monica; Leybold, Milena; Kenney, Sean C. (Organization studies, 2024)
Platform organizing does not unfold in a neutral realm. While interconnected communicative acts such as posts, shares, or likes constitute organizing on social media platforms, platform organizations condition how such platform organizing unfolds through content moderation. This study engages with the concept of contributorship, which is anchored in communication constitutes organization (CCO) scholarship, and theorizes content moderation as a process of authorization based on ‘norms of contributorship’. Applying queer theorizing to engage with norms as a site of power vis-a-vis embodied difference, we investigate poetic speech acts as queering endeavours that interrogate norms of contributorship in the constitution of platform organizing. Drawing upon a qualitative analysis of Instagram posts that challenge content moderation related to nudity as embodied difference, the findings reveal three practices of poetic speech – playfully altering, juxtaposing wor(l)ds and satirical challenging. Such practices skilfully repoliticize the entanglement of communication, control and normativity, and lay the foundation for collectively queering norms of contributorship in platform organizing. Building upon these insights, we highlight how organizational theory and practice are always implicated in normative regimes and underscore the need for attending to the existence of organizational subjects at and beyond the margins through queering organizing writ large.